2012
DOI: 10.1162/jinh_a_00303
|View full text |Cite
|
Sign up to set email alerts
|

Offspring Sex Preference in Frontier America

Abstract: Analysis of the fertility histories of women born between 1850 and 1900, as given in the Utah Population Database (UPDB), reveals the effect of the number, as well as the sex composition, of previous children on birth-stopping and birth-spacing decisions. Specifically, agricultural and Church of Jesus Christ of Latter-day Saints (LDS) households—two sub-populations that might have placed different values on male and female children for economic, social, and/or cultural reasons—showed a distinct preference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…The importance of the specific context in time and space for certain preferences regarding the sex composition of the sibling set is not only observed for mortality, but also for fertility outcomes. The main argument for this change is the shift in preferences that accompanied socio-economic change (Bohnert, Jåstad, Vechbanyongratana, & Walhout, 2012;Manfredini, Breschi, & Fornasin, 2016;Raley & Bianchi, 2006;Reher & Sandström, 2015). Sandström and Vikström (2015), for example, demonstratedby using Knodel's nineteenth-century German village genealogiesthat son preference influenced reproductive behaviour because parents who had only girls were more likely to have an additional child than those with a mixed sibling set.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the specific context in time and space for certain preferences regarding the sex composition of the sibling set is not only observed for mortality, but also for fertility outcomes. The main argument for this change is the shift in preferences that accompanied socio-economic change (Bohnert, Jåstad, Vechbanyongratana, & Walhout, 2012;Manfredini, Breschi, & Fornasin, 2016;Raley & Bianchi, 2006;Reher & Sandström, 2015). Sandström and Vikström (2015), for example, demonstratedby using Knodel's nineteenth-century German village genealogiesthat son preference influenced reproductive behaviour because parents who had only girls were more likely to have an additional child than those with a mixed sibling set.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the Netherlands and Spain (Reher and Sanz-Gimeno 2007;van Poppel et al 2012), in Tasmania, the number of surviving children had no significant association with the time to the next birth, indicating that couples were not adjusting their birth spacing in relation to the deaths of infants or children. Unlike Utah and Germany (Bohnert et al 2012;Sandström and Vikström 2015), but similar to Belgium (Alter et al 2010), in Tasmania, the sex composition of the family also had no significant association with stopping or spacing practices.…”
Section: Resultsmentioning
confidence: 90%
“…Preston (1978) suggests the replacement strategy may be related to the sex of the child who dies-that is, if the parents desire a certain number of sons and the child who dies is female, they may not make efforts to 'replace' this child. Studies of fertility in Utah (Bohnert et al 2012) and in Germany (Sandström and Vikström 2015) in the late 19th and early 20th centuries have shown families were more likely to progress to the next birth if they had only or mostly daughters. Alter et al (2010), on the other hand, found no such relationship between sex composition and fertility in Sart in Belgium in the 19th century.…”
Section: Infant and Child Mortalitymentioning
confidence: 99%
“…Nora Bohnert, Hilde Leikny Jåstad, Jessica Vechbanyongratana and Evelien Walhout, ‘Offspring sex preference in frontier America’, Journal of Interdisciplinary History , 42 (2012), 519–41.…”
mentioning
confidence: 99%
“…21 Nora Bohnert and her collaborators encounter the same son preference in the later births among rural Mormons in 19th-century Utah. 22 It would seem that demographers are beginning to come around to the conclusion that parents did indeed shape the number and the sex of their offspring as in Asia.…”
mentioning
confidence: 99%